CLINICAL-EPIDEMIOLOGIC PECULIARITIES AND STRUCTURE OF CHRONIC INFLAMMATORY JOINT DISEASES IN CHILDREN OF ROSTOV REGION - E.А. Ligostaeva; E.I. Alexeeva ("Paediatrician" Publishers LLC, 2011)
The article contains analysis of prevalence and primary disease rates data of inflammatory diseases of the joints in children of Rostov region. It has been shown that just epidemiologic study allows more precise evaluation of parameters under study. Judging by epidemiologic study results prevalence of juvenile arthritis among children in 2006 and 2010 was 61,9 and 85,0 per 100 000 accordingly. Official data, however, were almost twice lower: 30,7 and 38,4 per 100 000 children, accordingly. It has been proved that in overall structure of inflammatory diseases the leading position takes juvenile arthritis (51%), second place is occupied by reactive arthropathies (49%). First place is taken by Reiter syndrome (31%), second - by juvenile oligoarthritis (18%), third - by an ankylosing spondillitis (15%),fourth - postenterocolitic arthropathy (caused by Yersinia) (10%) and seronegative juvenile polyarthritis (10%).Key words: children, chronic joint diseases, juvenile arthritis, reactive arthritis, prevalence, clinical peculiarities. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 111-115)